Concurrent validity of walking speed values calculated via the GAITRite electronic walkway and 3 meter walk test in the chronic stroke population. (April 2014) - Peters, Denise M.; Middleton, Addie; Donley, Jonathan W.; Blanck, Erika L.; Fritz, Stacy L.
Abstract The purpose of this study was to provide novel information regarding the concurrent validity (primary aim) and reliability (secondary aim) of walking speed (WS) calculated via the GAITRite electronic walkway system and 3 meter walk test (3MWT) in the chronic stroke population. The 3MWT is a feasible option for clinicians working in environments where space is limited. Psychometric properties of the test have not been established. Participants with chronic stroke were stratified into three groups: (1) household ambulators (HA) (self-selected WS < 0.4 m/s, 12 participants, 31 observations); (2) limited community ambulators (LCA) (self-selected WS 0.4–0.8 m/s, 24 participants, 60 observations); and (3) community ambulators (CA) (self-selected WS > 0.8 m/s, 26 participants, 71 observations). Three consecutive trials of GAITRite and 3MWT were performed at participant's self-selected WS. Average WS measurements differed significantly (p < 0.05) between GAITRite and 3MWT for all three groups. HA group: GAITRite 0.25 (0.11) m/s, 3MWT 0.27 (0.11) m/s; LCA group: GAITRite 0.56 (0.11) m/s, 3MWT 0.52 (0.10) m/s; CA group: GAITRite 1.03 (0.16) m/s, 3MWT 0.89 (0.15) m/s. Both WS measures had excellent within-session reliability (ICC's ranging from 0.85 to 0.97, SEM95 from 0.04 to 0.12 m/s and MDC95 from 0.05 to 0.16 m/s). Reliability was highest for HA on both measures. Although both the 3MWT and the GAITRite are reliable measures of WS for individuals with chronic stroke, the two measures do not demonstrate concurrent validity.